ANALYSIS OF CRYSTALLINE PHASE AND FUNCTIONAL GROUPS OF ZnO FROM PINEAPPLE PEEL EXTRACT - Santika, Rosalia; Rohmawati, Lydia (Indonesian Physical Review, 2022)
The use of pineapple peel has not been paid attention to because of the lack of public knowledge regarding the content and benefits of pineapple skin. However, it can use pineapple skin for herbal drinks and animal feed. Pineapple peel has phytochemical compounds and bioactive compounds such as ZnO. Therefore, this study was conducted to determine ZnO's crystalline phase and the functional group from pineapple peel extract. Synthesis of ZnO from pineapple peel extract used the green synthesis method, with the following steps: pineapple peel was pounded and stirred by heating at 80Â°C, and then ultrasonicated. The solution was added with NaOH and centrifuged at 4000 rpm. This result is heated at a temperature of 120Â°C with a 6 and 12 hours holding time. After that, it cooled to room temperature. The results of XRD analysis obtained the optimal ZnO crystalline phase at a holding time of 12 hours according to the pdf cards database (96-210-7060) and nanocrystalline size of 17.55 nm. The FTIR results on the ZnO sample had an absorption peak of 4000-400cm-1 with functional groups O-H alcohol and phenol, -C=C alkene, C=O, C-O, C-N, and Zn-O. It is hoped to be applied later in the medical and industrial fields by obtaining ZnO samples from pineapple peel extract